Quantification of arbuscular mycorrhizal fungal DNA in roots: how important is material preservation? - Janoušková, Martina; Püschel, David; Hujslová, Martina; Slavíková, Renata; Jansa, Jan (Mycorrhiza, 2015)
Monitoring populations of arbuscular mycorrhizal fungi (AMF) in roots is a pre-requisite for improving our understanding of AMF ecology and functioning of the symbiosis in natural conditions. Among other approaches, quantification of fungal DNA in plant tissues by quantitative real-time PCR is one of the advanced techniques with a great potential to process large numbers of samples and to deliver truly quantitative information. Its application potential would greatly increase if the samples could be preserved by drying, but little is currently known about the feasibility and reliability of fungal DNA quantification from dry plant material. We addressed this question by comparing quantification results based on dry root material to those obtained from deep-frozen roots of Medicago truncatula colonized with Rhizophagus sp. The fungal DNA was well conserved in the dry root samples with overall fungal DNA levels in the extracts comparable with those determined in extracts of frozen roots. There was, however, no correlation between the quantitative data sets obtained from the two types of material, and data from dry roots were more variable. Based on these results, we recommend dry material for qualitative screenings but advocate using frozen root materials if precise quantification of fungal DNA is required.
Keywords: DNA fungální; ochrana biologická; Medicago truncatula; DNA, Fungal; Plant Roots; kořeny rostlin; mykorhiza; Preservation, Biological; Mycorrhizae